First report of cross resistance to silver and antibiotics in Klebsiella pneumoniae isolated from patients and polluted water in Tunisia. (25th November 2020) - Ben Miloud, Samar; Ali, Md Muntasir; Boutiba, Ilhem; Van Houdt, Rob; Chouchani, Chedly
Abstract: Klebsiella pneumoniae, ubiquitously found in a variety of environmental sources, is an important pathogen in burn wounds and nosocomial infections. Burn wounds have been commonly treated with silver compounds, which are also used in a multitude of (non)medical products. As the latter increased silver discharge into different environments, we evaluated and compared silver resistance in K. pneumoniae isolates collected from patients hospitalized at the Charles‐Nicolle hospital (Tunis, Tunisia) with isolates collected from different metal polluted waters in the north and south of Tunisia. All K. pneumoniae isolates harboured bla TEM‐1 and bla SHV‐1 . In addition, all clinical isolates showed a multidrug phenotype and harboured the bla CTX‐M‐15, bla OXA‐1 and bla NDM‐1 . Furthermore, all isolates showed resistance to silver nitrate. The silver resistance determinant, screened via the silE gene, was located for all isolates on a large plasmid with a size similar to pMG101. This study showed cross‐resistance between silver and beta‐lactams in clinical as well as environmental K. pneumoniae isolates from Tunisia and showed for the first time that NDM‐1‐producing K. pneumoniae developed resistance to silver.